2015
DOI: 10.1051/epjconf/20159202110
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the interaction of two cylinders in the flow pattern

Abstract: ([SHULPHQWDO LQYHVWLJDWLRQ RI WKH LQWHUDFWLRQ RI WZR F\OLQGHUV LQ WKH IORZ SDWWHUQ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Figure 8 shows a previous visualization result [10] and the visualization result obtained in this experiment. Here, although both have some difference at experimental conditions, it is a comparatively near case.…”
Section: Comparison Of Aspect Of Flow By Different Visualization Techmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 8 shows a previous visualization result [10] and the visualization result obtained in this experiment. Here, although both have some difference at experimental conditions, it is a comparatively near case.…”
Section: Comparison Of Aspect Of Flow By Different Visualization Techmentioning
confidence: 99%
“…Yokoi and Hirao [5][6][7][8][9] is reporting the result of the study shown by the streak line about the vortex shedding from the circular cylinder which is oscillating in the direction of flow using the flow visualization technique based on a pouring streak method. Rut et al [10,11] is reporting the result of study which showed the interference flow from two circular cylinders arranged staggered using the flow visualization technique based on a suspension method by the particle pass line. Then, the visualization experiment by the streak line method was performed on the same conditions as a previous experiment for the database creation in comparison with the previous experimental result [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article describes an experimental measurement of the influence of cylinders in the flow field in staggered configuration using the CTA method and presents the results of these measurements. This paper follows the measurements published in [7]. …”
mentioning
confidence: 63%
“…This paper is based on measurements published in [1] and [2]. These articles outline the influence of the secondary cylinder on the wake of the primary cylinder for various combinations of staggered configuration.…”
Section: Introductionmentioning
confidence: 99%